Nutrition in public health principles, policies, and practice - Spark, Arlene, 1945-; Dinour, Lauren M.; Obenchain, Janel (CRC Press, Taylor & Francis Group, 2016)
"Examines the application of nutritional policy to dietary guidance, health promotion, and the practice of public health nutrition. The book has been updated to maintain relevancy of nutrition information, references, and resources. Highlights from the second edition: legislation such as the Healthy, Hunger-Free Kids Act of 2010, Agricultural Act of 2014 (Farm Bill), and proposals for the next Farm Bill; discussions of study designs, the SEED-SCALE model for health promotion, health disparities and health equity, worksite wellness, Let's Move!, and other initiatives; impact of the ACA on menu labeling policies, the Ryan White HIV/AIDS Act, and legislation regarding breastfeeding; examination of health disparities, demographic trends, and health literacy, sexual orientation, gender identity, and gender expression, and the role of social media in tailored health communications; 2010 Dietary Guidelines with analysis of potential upcoming changes in 2015 dietary guidelines, Healthy Eating Index 2010, My Plate, and Harvard Healthy Eating Plate; [and] Best Bones Forever! campaign, text messaging for tailored health communication, and 4-day throw away study assessing the use of social media for education regarding food safety"-- Provided by publisher